Development of a resonant frequency converter for partial discharge tests on potential transformers - Yutthagowith, P.; Prombud, T.; Leelachariyakul, B. (My University, 2018)
In this paper, the development of a partial discharge testing system based on a resonant frequency converter for potential transformers (PTs) is presented. The system is composed of a power low-voltage variable frequency converter connected with a frequency tuning circuit, a high-voltage testing transformer, and a conventional partial discharge detection system. The performances of the developed system in comparison with the conventional PWM frequency converter were investigated terms of the quality of the output voltage from the high-voltage testing transformer, i.e. the voltage difference (peak voltage/square root of 2 and rms voltage), total harmonic distortion of the output high voltages (THDv), and background noises in the partial discharge test. It is found that the developed system based on the resonant frequency converter provides the better performances (in terms of the output voltage from a testing transformer, the voltage difference, THDv, and background noise) than those of the PWM converter. The voltage difference and THDv are lower than 2%, and the background noise is less than 2.5 pC. In addition, the developed system has been used for the real partial test on a potential transformer in the distribution system successfully. The developed inverter is an attractive choice in the PD tests of potential transformers.
Keywords: high-voltage tests; partial discharge; potential transformer; power variable frequency converter; resonant circuit